Effects of Dietary Direct Fed Microbial Supplementation on Performance, Intestinal Morphology and Immune Response of Broiler Chickens Challenged With Coccidiosis - Calik, Ali; Omara, Islam I.; White, Mallory B.; Li, Wenting; Dalloul, Rami A. (Frontiers in Veterinary Science, 2019)
Poultry coccidiosis is a costly intestinal disease that leads to considerable tissue damage, inefficient nutrient absorption, increased mortality, and predisposition to secondary infections. This study evaluated the effects of a direct feed microbial (DFM) dietary additive on performance, intestinal morphology and immune response of broilers during a mixed coccidiosis challenge. In total, 840 Cobb500 male broilers were randomly allocated to 3 treatments (7 replicates, 40 birds/pen) including negative control (NC) fed basal diet; positive control (PC) fed basal diet with coccidiosis challenge; and DFM supplemented diet, with coccidiosis challenge. At 15 d of age, all birds except for the NC treatment were orally gavaged with live oocysts of a commercial vaccine. On d 21 (6 d post challenge), 4 birds/pen were randomly selected and euthanized for scoring of coccidia-caused lesions in the duodenum, jejunum, and ceca. Body weight gain (BWG), feed intake (FI) and feed conversion ratio (FCR) were recorded on d 7, 14, 28, and 42. Jejunal and ileal tissue samples were taken for histomorphological assessment from 2 birds/pen on d 21. Ileal samples were also taken for mRNA expression analysis on d 14 and d 21. The DFM birds had significantly greater BWG than PC birds during d 0-21 (P < 0.05). No differences were observed among the treatment groups in terms of FI and FCR. Dietary DFM supplementation significantly reduced lesion scores in the duodenum and jejunum when compared with PC group (P < 0.05). The coccidia challenge significantly reduced (P < 0.05) ileal villus height when compared to non-challenged group on d 21. Conversely, dietary DFM supplementation alleviated the negative effects of coccidiosis by increasing ileal villus area on d 21 (P < 0.05). The challenged birds had significantly greater expression of IFN-γ and IL-1β in the ileum on d 21. Based on these findings, dietary DFM supplementation may help restore broiler performance during the starter and early grower periods during coccidiosis, likely by maintaining gut integrity via improving intestinal morphology and also by reducing disease severity as manifested by lower lesion scores.